Interrelation of mental toughness, religiosity, and happiness of elite adolescent athletes based on gender, type of sport, and level of education - Yos Wandik; Dina Dina; Tri Setyo Guntoro; Sutoro Sutoro; Oscar Oswald Oktovianus Wambrauw; Fitrine Christiane Abidjulu; Semuel Piter Irab; Trajanus Laurens Jembise; Tery Wanena; Remuz Maurens Bertho Kmurawak; Agnes Supraptiwi Rahayu; Janviter Manalu; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
There are no studies that comprehensively discuss mental toughness, religiosity, and satisfaction based on gender, type of sport, and different school levels, especially in the context of elite youth athletes. In fact, this variable is believed to be a very important construct in relation to athletes' performance and achievements on the field. The purpose of this research is to explore athlete’s mental toughness, religiosity, and life happiness based on gender, type of sport, and school level. A total of 97 elite youth athletes were included in the study (age = 15.22 ± 1.34; F = 36, M = 61). Research data were collected using standard instruments used by scientists around the world, namely the Mental Toughness Index (MTI), Spirituality in Sports Test (SIST), and Satisfaction with Life Scale (SWLS). Analysis of variance, correlation, and path analysis were used to understand more deeply the three research variables based on the athlete’s gender, type of sport, and school level. This study found that there was a significant difference only in the athlete's religiosity variable based on school level (F = 6.212, p ≤ .01). Athletes' mental toughness has a significant relationship with religiosity (r = .343; ρ = .323; p ≤ .01) and happiness in life (r = .340; ρ = .200; p ≤ .01). Apart from that, it also appears that religiosity has a significant relationship with happiness in life (r = .475; ρ = .406; p ≤ .01) and athlete age is significantly correlated with religiosity (r = .233; ρ = .200; p ≤ .05). Athletes' mental toughness has a significant relationship directly to satisfaction and indirectly through religiosity. These three variables have an important role in competitive sports so coaches or athlete coaches need to provide psychological intervention to improve these three variables.